Penyelesaian Sengketa Pertanahan Secara Non Litigasi Di Kantor Pertanahan Kabupaten Lombok Timur - Khatirah Juhaini, Nur Ilmi; Andriyani, Shinta (Fakultas Hukum Universitas Mataram, 2024)
This research aims to determine the extent of the non-litigation land dispute resolution process at the East Lombok Regency Land Office and determine the obstacles and supporting factors in implementing non-litigation land dispute resolution at the East Lombok Regency Land Office. This research uses empirical legal research with statutory, conceptual, and sociological approaches. The research study shows that non-litigation land dispute resolution at the East Lombok Land Office uses a mediation mechanism, namely case review, summons to the parties to the dispute, mediation, and agreement. From the results of the implementation of non-litigation dispute resolution, some cases cannot resolved by non-litigation. Because in its implementation, there are inhibiting and supporting factors in non-litigation dispute resolution.